Phenotypic and Genotypic Characterization of ESBL-, AmpC-, and Carbapenemase-Producing Klebsiella pneumoniae and Escherichia coli Isolates - Kazemian, Hossein (Med Princ Pract, 2019)
OBJECTIVES: Drug resistance among gram-negative bacteria is a worldwide challenge. Due to the importance of drug-resistant Klebsiella pneumoniae and Escherichia coli strains in hospital-acquired infections, we aimed to determine the phenotypic and genotypic characteristics of ESBL-, AmpC-, and carbapenemase-producing isolates obtained from hospitalized patients in Tehran and Ilam (Iran). MATERIALS AND METHODS: In total, 90 K. pneumoniae isolates and 65 E. coli isolates were collected from various infections. Phenotypic identification of bacterial isolates was performed using standard methods. Phenotypic screening of ESBL, AmpC, and carbapenemase enzymes was carried out. Detection of ESBL, AmpC, and carbapenemase genes was also performed by the PCR method. RESULTS: Phenotypic detection tests showed that 36 (40%) K. pneumoniae and 23 (35.4%) E. coli isolates were ESBL producers. Moreover, 18 (20%) and 6 (9.2%) K. pneumoniae and E. coli isolates were AmpC producers, respectively. Modified Hodge test results indicated that 39 (43.3%) K. pneumoniae and 18 (27.7%) E. coli isolates produced carbapenemase. Molecular tests showed that 40% of K. pneumoniae and 36.9% of E. coli isolates were ESBL positive. AmpC was detected in 24.4 and 13.8% of K. pneumoniae and E. coli isolates. Carbapenemase was detected in 34 (37.8%) K. pneumoniae and 13 (20%) E. coli isolates. CONCLUSION: In this study, 3 K. pneumoniae isolates simultaneously carried ESBL, AmpC, and carbapenemase genes. Up-to-date strategies such as combination therapy or utilization of new antimicrobial agents might help to combat such drug-resistant organisms.